An impulsive model predictive static programming based station-keeping guidance for quasi-halo orbits. (November 2021) - Vutukuri, Srianish; Padhi, Radhakant
Abstract: In this paper, a control effort minimizing optimal station-keeping guidance is designed and implemented to regulate a spacecraft around an L 1 quasi-halo orbit in the Sun–Earth–Moon elliptic four-body problem. The station-keeping guidance is formulated as a finite time, non-linear optimal control problem with hard terminal output constraints and Impulsive Model Predictive Static Programming (I-MPSP) is used to obtain station-keeping maneuvers. The algorithm is iterative, where the guessed station-keeping maneuvers are optimally updated by a simple closed-form equation until an output terminal constraint is satisfied and an optimal cost function is obtained. The technique involves the calculation of sensitivity matrices that is done in a computationally efficient manner owing to their recursive nature. Through extensive simulations, in the presence of disturbance forces and uncertainties, a closed-loop application of I-MPSP guidance results in a trajectory that remains tightly bound to the reference orbit over a long-duration mission. Highlights: Impulsive MPSP guidance is proposed for station keeping on quasi-halo orbits. This computational guidance ensures control energy minimization. It exhibits rapid convergence and demands minimal computational time. Robustness analysis shows it can effectively handle disturbances and uncertainties. Spacecraft trajectories are tightly bound to the reference orbit during the entire mission.